Augustine on angelic knowledge - Ovie Valentine Aghoghophia (Warszawskie Studia Teologiczne)
Angelic beings are spiritual intellectual beings. They possess knowledge; however, they are not omniscient. They are spiritual beings with limited knowledge in comparison to God, which means they are not like God who is the fullness of knowledge, they acquire knowledge. So, how do angelic beings acquire knowledge? What is the source of their knowledge? What is the nature of the angelic beings’ knowledge? What can angelic beings know and not know? What do these spiritual beings do with their angelic knowledge? Is there any difference between the fallen angels’ knowledge and the upright angels’ knowledge? What is the object of these spiritual intellectual beings’ knowledge? Augustine answered these questions in his theology of angelic knowledge. Augustine treated the nature of the knowledge the angels can acquire with their natural angelic faculty and the nature of the knowledge they acquire through the grace of God. Divine illumination is equally enjoyed by the angels and even more than humans do. The angels are lovers of the truth and they seek the truth either with the appropriate or inappropriate use of their will. The kind of knowledge they pursue determines their relationship with the creator. Augustine outlined how knowledge separates the good angels from the bad angels. These and more are what this paper seeks to explore.